Implementación Eficiente en la Confección de un Frente de Pareto co-objetivo para el mecanismo de Matchtracking del Algoritmo Fuzzy ARTMAP - Figueroa-Flores, Nuria Vanessa (Instituto Tecnológico de Costa Rica, 2014)
Matchtracking mechanism is integral to the Fuzzy ARTMAP, it iterates over the set of templates seeking the w corrected template class that best represents the input pattern I. We propose to visualize this mechanism with a search within a Pareto front built appropriately to a problem in co-single valued objective optimization, which achieves an improvement in the complexity of O(n) a O(log(n)).
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2014.
Keywords: Redes Neurales; ARTMAP; Fuzzy ARTMAP; Matchtracking; Optimización; Research Subject Categories::TECHNOLOGY::Information technology::Computer engineering